Prevalence of potential risk of eating disorders among young, unprofessional European athletes: results of the ERASMUS+ project SCAED - Kenđel Jovanović, Gordana; Čulina, Tatjana (Frontiers in Nutrition, 2024)
Introduction: Adolescent athletes are at higher risk of developing eating disorders (ED) due to sports environment pressures and developmental characteristics. The ERASMUS+ project Sports Community against Eating Disorders (SCAED) aims to assess the prevalence of the potential risk of eating disorders among young, unprofessional European athletes and to provide them with easier access to professional support and knowledge.Methods: The online survey included 462 unprofessional athletes from six European countries aged 12 to 25 (average age 18.49 ± 5.50) on their socio-demographics, sports and lifestyle habits, behaviors, concerns, and perceived pressure from coaches and teammates regarding body weight and shape. The eating disorders potential risk was assessed using the Eating Disorder Examination for Adolescents (EDE-A) and Eating Disorders Screen for Athletes (EDSA).Results: Every seventh (14.9%, EDE-A) and fifth (19.9%, EDSA) of young, unprofessional European athletes were at possible risk for developing eating disorders. Overall potential risk (18.7% EDE-A; 26.6% EDSA), dietary restraint (12.9%) and concerns about eating (9.5%), shape (23.7%), and weight (19.6%) were significantly more prevalent among female athletes. Younger athletes showed a slightly higher prevalence and avoidance of food. Athletes training in weight-sensitive sports exhibited more behaviors related to eating disorders. Females (p=0.003), younger and those athletes training in less weight-sensitive sports noted higher weight-and shape-related pressure from coaches. Dissatisfaction with their current weight expressed 44.6% of athletes, while 46.1% thought that they needed to lose weight to improve performance.The observed prevalence of the potential risk of ED among young, unprofessional European athletes is concerning, particularly due to limited access to support. Efforts to reduce the prevalence should target female and younger athletes in weight-sensitive sports. The SCAED Erasmus+ project aims to decrease ED prevalence among young, unprofessional European athletes, their families, and coaches by supporting with through education and professional consultation.